(untitled) (The Review of Diabetic Studies, 2024)
Background and Significance: The diagnosis of cancer in a child represents a seismic disruption to the family system, precipitating a complex trajectory of physiological, psychological, and social distress. As pediatric oncology survival rates improve due to biomedical advances, the chronicity of caregiving has emerged as a critical public health concern. Primary caregivers, predominantly parents, face "caregiver burden"—a multidimensional construct encompassing financial toxicity, physical exhaustion, and role entrapment—and "compassion fatigue," a form of secondary traumatic stress resulting from prolonged exposure to their child’s suffering. The intersection of nursing and social work (SW) disciplines offers a unique "bio-psychosocial" mechanism to mitigate these effects. Objectives: This systematic review aims to exhaustively evaluate the prevalence and phenomenology of caregiver burden and compassion fatigue within pediatric oncology populations. Furthermore, it seeks to analyze the efficacy of interdisciplinary interventions led by nursing and social work professionals, specifically comparing educational, counseling, and problem-solving modalities. Methods: A rigorous systematic review of the literature was conducted, synthesizing data from randomized controlled trials (RCTs), quasi-experimental studies, and qualitative inquiries published through 2023. Key interventions analyzed include the Bright IDEAS problem-solving skills training, the Telephone Interpersonal Counseling (TIPC) model versus Supportive Health Education (SHE), and the PediQUEST symptom monitoring system. Results: Analysis indicates that approximately 50% of caregivers report high emotional stress, with significant prevalence of depression (32%) and anxiety (28.6%). The burden is dynamic, often peaking during the diagnostic phase and paradoxically resurfacing during survivorship due to fear of recurrence. Evidence demonstrates a distinct dichotomy in intervention efficacy: nurse-led educational interventions (SHE) effectively reduce anxiety and increase self-efficacy regarding symptom management, while social work-led interpersonal counseling (TIPC) is superior for alleviating depressive symptoms and social isolation. The Bright IDEAS program consistently demonstrates reductions in maternal mood disturbance. However, the implementation of these interventions is frequently hampered by systemic barriers, including critical staffing shortages (e.g., 1 social worker per 40 patients) and siloed professional practices. Conclusions: The mitigation of caregiver burden requires a structured, interdisciplinary approach that integrates the medical expertise of nursing with the psychosocial expertise of social work. Ad hoc support is insufficient; evidence-based protocols such as TIPC and Bright IDEAS must be embedded into standard care to preserve the family unit’s integrity and optimize patient outcomes.